Digital Da'wah Communications for The Prosperous Justice Party During The Covid-19 Pandemic - Khoiruddin Muchtar; Marlida Maulidawati (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study aims to identify da'wah messages on the TikTok @pksejahtera account during the Covid-19 pandemic related to denotative, connotative, and mythical meanings in da'wah content on the TikTok @pksejahtera account limited to tausyiah content from da'i to mad'u with the hashtag #tausyiah , #habib, #Islam, #pkspelayanrakyat, #remembrance, #PKS, #Bertualangrasa, #tausyiahislam, #minitausyiah, #tausyiahhabibsalim, #ramadhan2021, and #syekhalijaber. This study uses a semiotic analysis method with a qualitative approach. The results showed that denotative Meaning could be observed from the choice of words and the arrangement of sentences in the text; connotative Meaning can be observed from the video images displayed in each scene. In contrast, the Meaning of myth can be found in the da'wah content on the TikTok @pksejahtera account by observing the preacher when delivering tausyiah.Penelitian ini bertujuan untuk mengidentifikasi pesan dakwah pada akun TikTok @pksejahtera selama pandemi Covid-19 terkait dengan makna denotatif, konotatif, dan mitos dalam Konten dakwah pada akun TikTok @pksejahtera dibatasi pada konten tausyiah dari da’i kepada mad’u dengan tagar #tausyiah, #habib, #Islam, #pkspelayanrakyat, #zikir, #PKS, #Bertualangrasa, #tausyiahislam, #minitausyiah, #tausyiahhabibsalim, #ramadhan2021, dan #syekhalijaber. Penelitian ini menggunakan metode analisis semiotika dengan pendekatan kualitatif. Hasil penelitian menunjukan bahwa, makna denotatif dapat diamati dari pemilihan kata dan penyusunan kalimat dalam teks, makna konotatif dapat diamati dari gambar video yang ditampilkan dalam tiap adegan, sedangkan makna mitos dapat ditemukan dalam konten dakwah pada akun TikTok @pksejahtera dengan mengamati da’i saat menyampaikan tausyiah.